Formation and control of nitrogenous DBPs from Western Australian source waters: Investigating the impacts of high nitrogen and bromide concentrations - Kristinana, I.; Liew, D.; Henderson, R.; Joll, Cynthia; Linge, K. (2017)
We studied the formation of four nitrogenous DBPs (N-DBPs) classes (haloacetonitriles, halonitromethanes, haloacetamides, and N-nitrosamines), as well as trihalomethanes and total organic halogen (TOX), after chlorination or chloramination of source waters. We also evaluated the relative and additive toxicity of N-DBPs and water treatment options for minimisation of N-DBPs. The formation of halonitromethanes, haloacetamides, and N-nitrosamines was higher after chloramination and positively correlated with dissolved organic nitrogen or total nitrogen. N-DBPs were major contributors to the toxicity of both chlorinated and chloraminated waters. The strong correlation between bromide concentration and the overall calculated DBP additive toxicity for both chlorinated and chloraminated source waters demonstrated that formation of brominated haloacetonitriles was the main contributor to toxicity. Ozone–biological activated carbon treatment was not effective in removing N-DBP precursors. The occurrence and formation of N-DBPs should be investigated on a case-by-case basis, especially where advanced water treatment processes are being considered to minimise their formation in drinking waters, and where chloramination is used for final disinfection.